2021
DOI: 10.1002/jmv.27293
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of mutation and vaccination on spread, severity, and mortality of COVID‐19 disease

Abstract: Coronavirus disease 2019 (COVID‐19) has had different waves within the same country. The spread rate and severity showed different properties within the COVID‐19 different waves. The present work aims to compare the spread and the severity of the different waves using the available data of confirmed COVID‐19 cases and death cases. Real‐data sets collected from the Johns Hopkins University Center for Systems Science were used to perform a comparative study between COVID‐19 different waves in 12 countries with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…COX enzymes are important for sufficient antibody production after vaccination. Thus, using NSAIDs decreases the production of antibodies after coronavirus vaccination or infection [15,25].…”
Section: Discussionmentioning
confidence: 99%
“…COX enzymes are important for sufficient antibody production after vaccination. Thus, using NSAIDs decreases the production of antibodies after coronavirus vaccination or infection [15,25].…”
Section: Discussionmentioning
confidence: 99%
“…Some people use non-steroidal anti-inflammatory drugs (NSAIDs) to treat post-coronavirus vaccine symptoms. Some studies reported concerns about using NSAIDs for treating symptoms of coronavirus or post coronavirus vaccine symptoms [11,21]. NSAIDs inhibit cyclooxygenase 1 (COX 1) and cyclooxygenase 2 (COX 2) enzymes and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs inhibit cyclooxygenase 1 (COX 1) and cyclooxygenase 2 (COX 2) enzymes and inflammatory cytokines. Cox enzymes are necessary for the production of sufficient antibodies in response to coronavirus vaccine or infection [11,21]. Therefore, the use of NSAIDs may reduce the production of antibodies in response to coronavirus vaccination or infection [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the beginning of pandemic estimated overall hospital mortality from COVID-19 are approximately 15% to 20%, but up to 40% among patients requiring ICU admission; however, mortality rates vary across age cohorts, from 5% among patients younger than 40 years to greater than 60% for patients aged 80 to 89 years [ 4 ]. In contrast, a recent study suggested lower mortality due to the presence of appropriate treatment and vaccination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%